HAMBATAN BELAJAR PESERTA DIDIK PADA PROSES PEMBELAJARAN DI KELAS IV SD NEGERI 2 SOKARAJA BANJARNEGARA - Dewi Irma Ardiningrum; Ana Andriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the learning barriers faced by students in the learning process in grade IV at SD Negeri 2 Sokaraja Banjarnegara. The main focus of the study covers cognitive aspects that influence the learning process in the classroom. The method used is a qualitative approach with observation, interviews, and documentation techniques. The results of the study show that students have difficulty understanding memorization material, reading story questions, and constructing sentences when writing. The students' concentration levels are low, they are easily distracted by their surroundings, and they tend to be passive. The students are unable to respond to the teacher's explanations to the fullest extent. Some students exhibit hyperactive behavior. This study aims to identify the forms of learning barriers experienced by students and the efforts made by teachers to overcome these barriers in the classroom environment. Learning media are limited to pictures, videos, and textbooks. The teaching methods used are lecture-based and lack variety. The home learning environment is not supportive, as students do not receive tutoring because they live with their grandparents. There is a high dependence on gadgets, and material review at home is rarely done. School facilities are minimal, and there are no special programs available for students with learning difficulties. Teachers have made efforts to establish personal communication, but these efforts have not yet yielded significant results. Learning evaluations indicate that most students are unable to complete assignments independently. The learning process is not optimal and does not address the learning needs of all students.